DISKURSUS EPISTEMOLOGI DALAM PEMIKIRAN ISLAM KONTEMPORER - Zulfis Zulfis (Turast: Jurnal Penelitian dan Pengabdian, 2015)
This article discusses and explores how important epistemology in developing human thought and civilizationincluding in contemporary Islamic thought. After explaining the terms of epistemology and contemporaryIslamic thought, I outline some trends or models of contemporary Islamic epistemology based on Muslimsthinkers and intellectuals. Although their methodologies and approaches are different from each other, most ofthe trends, models and concepts of contemporary epistemology in Islam have been concorded with the modernand postmodern world views, the development of science, and social-cultural of mankind without ignoringthe basic principles of Islamic teachings.